Advanced cutting tools and technologies for drilling carbon fibre reinforced polymer (CFRP) composites: A review - Geier, Norbert; Davim, J. Paulo; Szalay, Tibor (Composites. Part A, Applied science and manufacturing, 2019)
Carbon fibre reinforced polymer (CFRP) composites have excellent specific mechanical properties, these materials are therefore widely used in high-tech industries like the automobile and aerospace sectors. The mechanical machining of CFRP composites is often necessary to meet dimensional or assembly-related requirements; however, the machining of these materials is difficult. In an attempt to explore this issue, the main objective of the present paper is to review those advanced cutting tools and technologies that are used for drilling carbon fibre reinforced polymer composites. In this context, this paper gives a detailed review and discussion of the following: (i) the machinability of CFRP including chip removal mechanisms, cutting force, tool wear, surface roughness, delamination and the characteristics of uncut fibres; (ii) cutting tool requirements for CFRP machining; and (iii) recent industrial solutions: advanced edge geometries of cutting tools, coatings and technologies. In conclusion, it can be stated that advanced geometry cutting tools are often necessary in order to effectively and appropriately machine required quality features when working with CFRP composites.